New insights into the putative role of leucine-rich repeat proteins of Leptospira interrogans and their participation in host cell invasion: an in silico analysis - Foltran, Bruno B.; Gaspar, João P.; Silva, Igor R. M.; Pires, Henrique M.; Andrade, Fernanda B.; Costa, Giovanna M.; Paixao, Julia E. L.; Fernandes, Luis G. V.; Teixeira, Aline F.; Nascimento, Ana L. T. O. (Frontiers in Cellular and Infection Microbiology, 2024)
Pathogenic Leptospira are spirochetes that cause leptospirosis, a worldwide zoonotic disease. Leptospirosis affects humans and animals, with approximately 1 million human infections and 60,000 deaths per year. The diversity of leptospiral strains and serovars allied to the fact that pathogenesis is not yet fully understood, make the development of an effective vaccine against leptospirosis a challenge. Outer membrane and secreted proteins are considered potential antigens since they play a vital role in mediating interactions with host molecules. Several domains or motifs have been reported to participate in the leptospiral infection process. Among them, leucine-rich repeat (LRR) proteins have been highlighted as attractive multipurpose proteins, exhibiting a broad spectrum of ligands and having a putative role in bacterial pathogenesis. Indeed, genome annotation of leptospiral species pointed out that LRR proteins are predominant in pathogenic strains, a feature that corroborates this hypothesis. A few LRR proteins of L. santarosai, L. borgpetersenii and L. interrogans have been studied and their possible role in virulence was proposed. Yet, a mechanistic and broad investigation of LRR proteins was not fully performed. In this review, a comprehensive in silico analysis of 21 LRR proteins of L. interrogans was performed in relation to structure, function, dynamics and virulent potential that will contribute to understanding the key role of these domains in the underlying mechanisms of leptospiral infection.